2020
DOI: 10.3390/ph14010021
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of Propyl-Propane-Thiosulfinate and Propyl-Propane-Thiosulfonate, Two Organosulfur Compounds from Allium cepa: In Vitro Antimicrobial Effect via the Gas Phase

Abstract: Propyl-propane thiosulfinate (PTS) and propyl-propane thiosulfonate (PTSO) are two volatile compounds derived from Allium cepa with a widely documented antimicrobial activity. The aim of this study was to evaluate their anti-candidiasis activity and the ability of its gaseous phase to inhibit bacterial and yeast growth in vitro. The minimum inhibitory concentration of various antifungal products (including PTS and PTSO) was determined versus 203 clinical isolates of Candida spp. through broth microdilution ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…However, the D pathotype appeared to be somewhat less affected to the gas phase of PTS and PTSO during the volatility-linked activity test, while the antifungal effect was quite more noticeable against the isolates of the ND pathotype. In line with our results, other authors have recently reported the antimicrobial activity of PTS and PTSO against bacteria and yeast through their gas phase [14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the D pathotype appeared to be somewhat less affected to the gas phase of PTS and PTSO during the volatility-linked activity test, while the antifungal effect was quite more noticeable against the isolates of the ND pathotype. In line with our results, other authors have recently reported the antimicrobial activity of PTS and PTSO against bacteria and yeast through their gas phase [14].…”
Section: Discussionsupporting
confidence: 93%
“…To study the antifungal activity of the compounds associated with their gas phase, the methodology described in Section 2.3.1 was carried out with some modifications [14,42].…”
Section: Antifungal Activity Of Gaseous Pts and Ptsomentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Lactobacillus and Bifidobacterium were the most resistant populations to these compounds. In line with these results, other articles reported the antibacterial activity of PTS and, especially, PTSO, against Gram-positive and Gramnegative human clinical isolates [52,87]. The results highlighted the special sensitivity of E. coli or Salmonella strains, regardless of their resistance to antibiotics such as cefotaxime or cefazidime, or their capacity to produce Extended-Spectrum Beta-Lactamase.…”
Section: Discussionsupporting
confidence: 65%
“…The results highlighted the special sensitivity of E. coli or Salmonella strains, regardless of their resistance to antibiotics such as cefotaxime or cefazidime, or their capacity to produce Extended-Spectrum Beta-Lactamase. Moreover, the activity against Gram-positive bacteria such as methicillin-resistant Staphylococcus aureus, Enterococcus faecalis and Streptococcus agalactiae was higher than the one observed against enterobacteria, especially in the case of PTSO [52,87].…”
Section: Discussionmentioning
confidence: 79%